Design, Synthesis, and Antiviral Activities of New Benzotriazole-Based Derivatives - Roberta Ibba; Paola Corona; Francesca Nonne; Paola Caria; Gabriele Serreli; Vanessa Palmas; Federico Riu; Simona Sestito; Maria Nieddu; Roberta Loddo; Giuseppina Sanna; Sandra Piras; et al. (MDPI AG, 2023)
Several human diseases are caused by enteroviruses and are currently clinically untreatable, pushing the research to identify new antivirals. A notable number of benzo[d][1,2,3]triazol-1(2)-yl derivatives were designed, synthesized, and in vitro evaluated for cytotoxicity and antiviral activity against a wide spectrum of RNA positive- and negative-sense viruses. Five of them (11b, 18e, 41a, 43a, 99b) emerged for their selective antiviral activity against Coxsackievirus B5, a human enteroviruses member among the Picornaviridae family. The EC50 values ranged between 6 and 18.5 μM. Among all derivatives, compounds 18e and 43a were interestingly active against CVB5 and were selected to better define the safety profile on cell monolayers by transepithelial resistance test (TEER). Results indicated compound 18e as the hit compound to investigate the potential mechanism of action by apoptosis assay, virucidal activity test, and the time of addition assay. CVB5 is known to be cytotoxic by inducing apoptosis in infected cells; in this study, compound 18e was proved to protect cells from viral infection. Notably, cells were mostly protected when pre-treated with derivative 18e, which had, however, no virucidal activity. From the performed biological assays, compound 18e turned out to be non-cytotoxic as well as cell protective against CVB5 infection, with a mechanism of action ascribable to an interaction on the early phase of infection, by hijacking the viral attachment process.